Multi-objective design optimisation: getting more for less - Evins,R; Joyce,SC; Pointer,P; Sharma,S; Vaidyanathan,R; Williams,C (Proceedings of ICE - Civil Engineering, 2012)
Multi-objective optimisation can help civil engineers achieve higher performance for lower costs in their designs. This is true whether ‘performance’ applies to structural strength or energy use, or whether ‘cost’ measures financial outlay or occupant satisfaction: if it can be quantified it can be optimised in some form. By exploring trade-offs between conflicting objectives and constraints, multi-objective optimisation enables informed decision-making. This paper outlines the principles and benefits of multi-objective optimisation and the means of implementation. The complementary aspects of parametric modelling and optimisation are discussed as an aid to the flexible design of buildings and structures. A range of real design problems are considered, including structural and environmental examples.